KiCad like a pro (Packt Publishing, 2017)
"This course is designed to teach you how to use KiCad assuming no prior knowledge in PCB design. My objective is to help you reach a high level of competency. You will be able to create any PCB that an Arduino or general electronics enthusiast can dream of. To achieve this, I have organized this course around three projects. With each project, I introduce several new KiCad features and extend your skill set. The ability to create a custom PCB is a core skill of an electronics enthusiast. Without the ability to create a custom PCB, your breadboard-based projects are doomed to oblivion. Learning how to use KiCad will make you a better maker because you will be able to create custom PCBs for your best designs, and as a result you will ensure that they realize their full potential."--Resource description page